UPAYA GURU PAI DALAM KURIKULUM 2013 DALAM PERSIAPAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR NEGERI 16 SUNGAI RINGIN - Hayatun Nisa; Aslan Aslan; Sri Sunantri (STKIP Melawi, 2021)
The importance of the curriculum that is carried out to answer the challenges of the changing times so that students are able to compete in the future. Another reason for making curriculum changes is considered burdensome for students, there is too much subject matter that students have to learn, thus making it overwhelmed. The 2013 curriculum is oriented to produce productive, creative, innovative and affective Indonesians through strengthening attitudes (know why), skills (know how), and knowledge (know why). The focus of this research is (1) how to challenge the 2013 Curriculum in preparation Learning Islamic Religion Education at Public Elementary School 16 Sungai Ringin Sintang District. This research method uses descriptive qualitative. This research was conducted at SD Negeri 16 Sungai Ringin having the address at Jalan Sintang Tempunak, Desa Kapuas Kanan Hilir, Sintang District. Primary data sources used include; Islamic Religious Education teachers, Curriculum Representatives, Principals and students. The techniques used in data collection are observation, interviews and documentation. Techniques in data collection are multiple sources of evidence (data triangulation), data reduction, data presentation and drawing conclusions and verification. The results of the research findings (1) the efforts of PAI curriculum 2013 teachers to prepare for Islamic Religious Education learning in maximizing the learning process following training and workshops to improve and develop teacher professionalism